Penggunaan Technology Acceptance Model untuk Mengidentifikasi Faktor-Faktor yang Berpengaruh dengan Penggunaan Sistem Informasi Pengelolaan Keuangan pada Pegawai di Perguruan Tinggi - Yuniatin, Tri (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Financial Management Information System (SIPK) is one of the determinants on the success of a university especially in Universitas Brawijaya (UB). The existence of Government Regulation of the Republic of Indonesia Number 61 of 1999 about the Establishment of Higher Education Institutions (universities) as a Legal Entity has produced a shift in the internal management system of a university. Therefore, SIPK is needed which is expected to simplify and accelerate the working results of employees. This can help to realize UB's vision and mission. A good SIPK is accepted by users. There are several factors that influence the use of SIPK so that it is necessary to identify these factors using Technology Acceptance Model (TAM). By knowing the factors that influence or not in using SIPK, it can be used as an evaluation for further improvement of SIPK in UB.